1989
DOI: 10.1002/jmor.1051990102
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of congenital microphthalmia in chicks (Gallus gallus)

Abstract: This study examines the morphology of sporadic congenital microphthalmia in 1-day-old chicks, with particular emphasis on the neural retina. On the basis of the size of the eyeball it is possible to classify microphthalmia into two groups, severe and mild. In severe microphthalmia (less than 5 mm in equatorial diameter), the eyeball is severely malformed, but in most cases it shows evidence of an organized neural retina. Although ganglion cells and an optic nerve head are present in a small proportion of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…It therefore appears that the critical event is significant cell loss that is not able to be reconstituted at later stages. In severe congenital microphthalmia, there is evidence of some organization of the neural retina even when a central connection is apparently absent (Ehrlich et al, 1989). This is consistent with the events occurring in heat-induced micrencephaly, where cell loss in neuroblast precursors can be up to 40% (Upfold et al, 1989) and some eye development has always been observed in guinea-pigs.…”
Section: Discussionsupporting
confidence: 77%
“…It therefore appears that the critical event is significant cell loss that is not able to be reconstituted at later stages. In severe congenital microphthalmia, there is evidence of some organization of the neural retina even when a central connection is apparently absent (Ehrlich et al, 1989). This is consistent with the events occurring in heat-induced micrencephaly, where cell loss in neuroblast precursors can be up to 40% (Upfold et al, 1989) and some eye development has always been observed in guinea-pigs.…”
Section: Discussionsupporting
confidence: 77%